Psychological factors and health-related quality of life in fibromyalgia patients - Ricardo P. Campos; Isabel Vázquez; Estela Vilhena (Health Psychology Report)
Background Fibromyalgia (FM) has been associated with decreased health-related quality of life (HRQoL), which has been linked to psychological variables such as anxiety, depression, coping, and social support. This study aimed to simultaneously analyse the association of these variables with HRQoL in FM patients and explore their mediating role in the relationship between somatic symptoms and HRQoL.